Report of a Working Group on Prunus (third meeting): Held at the ildungsstätte des deutschen Gartenbaues Grünberg, FRG, 24-26 November 1988 - International Board for Plant Genetic Resources (1988)
A Report of the ECPGR Prunus Working Group meeting, third meeting, 24-26 November 1988, Grünberg, Germany